Penggunaan Geogebra untuk Meningkatkan Pemahaman Matematis Mahasiswa dalam Menentukan Arah Kiblat - Nur Azmi; Laiyina Ukhti (Prodi Pendidikan Matematika, Fakultas Tarbiyah dan Ilmu Keguruan IAIN Langsa, 2023)
Abstract This research is motivated by the difficulties of students in understanding mathematical concepts, spesifically the geometry that used to determine the Qibla direction. The purpose of this study is to describe how to increase mathematical understanding of students skills to determine the Qibla direction by using the geogebra application. his research was conducted at the Sharia Faculty of Islamic Astronomy Department, IAIN Lhokseumawe. The sample of this study were all third semester students who were taking Geometry Astronomy courses. The data obtained through tests, interviews and questionnaires. Data analysis was carried out by means of descriptive and quantitative. The results showed that the increase in students' mathematical abilities reached 0.5 at the medium improvement criteria of N-Gain. From the results of the percentage of attitude scale questionnaires, it shows that the highest student response to geogebra is 93%, videlicet students give positive response for using of geogebra applications in geometry learning of the Qibla direction.